1995
DOI: 10.1172/jci118016
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between obesity and a marker near the tumor necrosis factor-alpha locus in Pima Indians.

Abstract: Because tumor necrosis factor-a (TNF-a) expression is increased in adipose tissue of both rodent models of obesity and obese humans, it has been considered as a candidate gene for obesity. Pima Indians were scored for genotypes at three polymorphic dinucleotide repeat loci (markers) near the gene TNF-a at 6p21.3. In a sib-pair linkage analysis, percent body fat, as measured by hydrostatic weighing, was linked (304 sib-pairs, P = 0.002) to the marker closest (10 kb) to TNF-a. The same marker was associated (P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 32 publications
7
61
0
2
Order By: Relevance
“…A potential role for the TNF-a locus in obesity is also supported by a linkage study, which reported a relationship between the TNF-a locus and various global measures of adiposity in Pima Indians and European Caucasians. 12,20 Thus, our data support the hypothesis that a genetic variant of the TNF-a gene may contribute to the development of obesity.…”
Section: Discussionsupporting
confidence: 84%
“…A potential role for the TNF-a locus in obesity is also supported by a linkage study, which reported a relationship between the TNF-a locus and various global measures of adiposity in Pima Indians and European Caucasians. 12,20 Thus, our data support the hypothesis that a genetic variant of the TNF-a gene may contribute to the development of obesity.…”
Section: Discussionsupporting
confidence: 84%
“…15 The TNFA locus has been linked to obesity. 170 One TNFA promoter SNP at position À308 that influences gene transcription has in a recent metaanalysis been associated with a modest increased risk of developing obesity, OR 1.23. 171,172 The C allele of one polymorphism in the IL6 promoter, ÀG174C, has in different populations been associated with obesity and decreased risk of T2DM.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…31 A polymorphism near the transcription start site of TNFa (G to A at position À308) has been associated with obesity in several populations. 32,33 It was recently found that the latter polymorphism only in¯uences body fat content in its homozygous form 34 in turn, suggesting that TNFa is a recessive obesity gene.…”
Section: Tumor Necrosis Factor Alpha (Tnfa)mentioning
confidence: 99%